Preparation of Chloramphenicol/Amino Acid Combinations Exhibiting Enhanced Dissolution Rates and Reduced Drug-Induced Oxidative Stress - Sterren, Vanesa Beatriz (2017)
Chloramphenicol is an old antibiotic agent that is re-emerging as a valuable alternative for the treatment of multidrug-resistant pathogens. However, it exhibits suboptimal biopharmaceutical properties and toxicity profiles. In this work, chloramphenicol was combined with essential amino acids (arginine, cysteine, glycine, and leucine) with the aim of improving its dissolution rate and reduce its toxicity towards leukocytes. The chloramphenicol/amino acid solid samples were prepared by freeze-drying method and characterized in the solid state by using Fourier transform infrared spectroscopy, powder X-ray diffraction, differential scanning calorimetry, scanning electron microscopy, and solid-state nuclear magnetic resonance. The dissolution properties, antimicrobial activity, reactive oxygen species production, and stability of the different samples were studied. The dissolution rate of all combinations was significantly increased in comparison to that of the pure active pharmaceutical ingredient. Additionally, oxidative stress production in human leukocytes caused by chloramphenicol was decreased in the chloramphenicol/amino acid combinations, while the antimicrobial activity of the antibiotic was maintained. The CAP:Leu binary combination resulted in the most outstanding solid system makes it suitable candidate for the development of pharmaceutical formulations of this antimicrobial agent with an improved safety profile.